Impact of human leukocyte antigen mismatch between donor-recipient on acute rejection in liver transplantation using next-generation sequencing: a single-center study - Lu, Genjie; Lu, Yangfang; He, Yanmin; Chen, Wei; Zhu, Faming (Frontiers in Immunology, 2025)
BackgroundThe effect of human leukocyte antigen (HLA) mismatch on acute rejection (AR) in liver transplantation (LT) is controversial. This study aimed to investigate the effect of donor-recipient mismatch at the HLA-A, -B, -C, -DRB1, -DRB3, -DRB4, -DRB5, -DQA1, -DQB1, -DPA1, and -DPB1 loci on AR in LT.MethodsIn total, 92 patients who underwent LT were selected for investigation from 1 January 2018 to 30 June 2024, and the donors of these patients were also from the same hospital. All donor and recipient specimens were genotyped via next-generation sequencing (NGS) for the 11 HLA loci. The patients were divided into AR and non-AR groups according to whether AR occurred after LT.ResultsA total of 12 cases (13.04%) experienced AR after LT. The proportion of chronic hepatitis B virus (HBV) infection was lower in the AR group than that in the non-AR group (P<0.05), while the proportion of split LT and mortality within 1 year after transplantation was higher in the AR group than in the non-AR group (P<0.05). Compared with the non-AR group, the AR group had a significantly higher proportion of high-mismatch DQB1 (2 vs. 0-1) and DRB1+DQB1 (4 vs. 0-3) (P<0.05) at the allele level, and other mismatches of a single locus and different combinations of the 11 HLA loci had no significant differences between the two groups (P>0.05). However, neither high-mismatch DQB1 nor high-mismatch DRB1+DQB1 at the allele level was an independent risk factor for AR after adjustment for chronic HBV infection, LT operative procedures, and immunosuppressive regimen using bootstrapping [odds ratio (OR): 0.203, 95% confidence interval (CI): 0.000–1.300, P=0.067; OR: 0.404, 95% CI: 0.000–2.625, P=0.172, respectively].ConclusionIn this preliminary study, no correlation between HLA mismatch at the allele level and post-transplant AR episodes was found.